2015
DOI: 10.1007/s11064-015-1808-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hybrid Tetrahydrobenzo[d]thiazole Based Aryl Piperazines D-264 and D-301 at D2 and D3 Receptors

Abstract: In elucidating the role of pharmacodynamic efficacy at D3 receptors in therapeutic effectiveness of dopamine receptor agonists, the influence of study system must be understood. Here two compounds with D3 over D2 selectivity developed in our earlier work, D-264 and D-301, are compared in dopamine receptor-mediated G-protein activation in striatal regions of wild-type and D2 receptor knockout mice and in CHO cells expressing D2 or D3 receptors. In caudate-putamen of D2 knockout mice, D-301 was ~ 3-fold more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Further, the positively charged piperazine nitrogen of 20 closest to the anisole moiety was found to interact with Asp110 3.32 (Figure 7B), the highly conserved aspartic acid residue found in TM3 of all biogenic amine GPCRs. 77 Given this observation, it is not surprising that compounds either lacking this nitrogen (50) or with immediately adjacent methyl groups (46 and 48) that could a K i (nM) values for the indicated compounds were determined as described in the Experimental Section. b NA indicates that the inhibition of binding was < 50% in the primary assay conducted using a single 10 μM concentration.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the positively charged piperazine nitrogen of 20 closest to the anisole moiety was found to interact with Asp110 3.32 (Figure 7B), the highly conserved aspartic acid residue found in TM3 of all biogenic amine GPCRs. 77 Given this observation, it is not surprising that compounds either lacking this nitrogen (50) or with immediately adjacent methyl groups (46 and 48) that could a K i (nM) values for the indicated compounds were determined as described in the Experimental Section. b NA indicates that the inhibition of binding was < 50% in the primary assay conducted using a single 10 μM concentration.…”
Section: T H Imentioning
confidence: 99%
“…R f = 0.48 (5% MeOH/ CH 2 Cl 2 ). 1 (50). A mixture of (4-(2-chloroethyl)piperidin-1-yl)(4-methoxyphenyl)methanone (64.9 mg, 0.230 mmol, 1.0 equiv), 4-methoxyphenol (32.0 mg, 0.258 mmol, 1.1 equiv), and potassium carbonate (57.0 mg, 0.412 mmol, 1.8 equiv) in DMF (1 mL) was heated at 55 °C for 19 h, followed by 80 °C for 45 h and then cooled to rt.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, the fold-selectivity decreased to 22-fold when tested in CHO cells expressing either human D 2 R or D 3 R [107]. In fact, D-264 stimulated [ 35 S]GTPγS binding to brain membranes prepared from wild-type mice, but had no efficacy in membranes from D 2 R KO mice, indicating that D-264 has little efficacy in vivo at the D 3 R, and that its functional effects are probably mediated by activation of the D 2 R, or possibly the D 4 R as it also displays significant affinity for the latter receptor subtype [113]. This study also found that the D 2 R and D 3 R expression levels in the heterologous CHO cells used were 2-fold and 135-fold, respectively, higher than those in rodent striatum, and the expression of the D 3 R was 10 times higher than that of the D 2 R in their cell model.…”
Section: D2r and D3r Selective Agonistsmentioning
confidence: 99%
“…This study also found that the D 2 R and D 3 R expression levels in the heterologous CHO cells used were 2-fold and 135-fold, respectively, higher than those in rodent striatum, and the expression of the D 3 R was 10 times higher than that of the D 2 R in their cell model. These factors could lead to artificially inflated D 3 R/D 2 R selectivity values, and the authors proposed the cautious interpretation of their results obtained from a single model system [113]. Treatment with D-264 improved movement in acute MPTP and lactacystin mouse models of PD [104].…”
Section: D2r and D3r Selective Agonistsmentioning
confidence: 99%
“…Based on these findings, the chemical scaffold of pramipexole was further used for discovery of selective agonists or partial agonists (Chen et al, 2008;Ghosh et al, 2010;Zhen et al, 2016). Drug design of selective D3R…”
Section: Accepted Manuscriptmentioning
confidence: 99%